Strategies under strategic uncertainty - Helene Mass (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
I investigate the decision problem of a player in a game of incomplete information who faces uncertainty about the other players' strategies. I propose a new decision criterion which works in two steps. First, I assume common knowledge of rationality and eliminate all strategies which are not rationalizable. Second, I apply the maximin expected utility criterion. Using this decision criterion, one can derive predictions about outcomes and recommendations for players facing strategic uncertainty. A bidder following this decision criterion in a first-price auction expects all other bidders to bid their highest rationalizable bid given their valuation. As a consequence, the bidder never expects to win against an equal or higher type and resorts to win against lower types with certainty.
Keywords: C72; D81; D82; D83; 330; Auctions; Incomplete Information; Informational Robustness; Rationalizability